AMPK activating and anti adipogenic potential of Hibiscus rosa sinensis flower in 3T3-L1 cells. (6th April 2019) - Lingesh, A.; Paul, David; Naidu, VGM.; Satheeshkumar, N.
Abstract: Ethnopharmacological relevance: The flowers of Hibiscus rosa sinensis has array of pharmacological actions. They are used in preparation of herbal decoction and teas, which have been used traditionally to reduce body weight and for its effect on metabolic syndrome. Aim of the study: To investigate the anti adipogenic efficacy of major fraction from ethyl acetate extract of the Hibiscus rosa sinensis flower at 25 and 50 µg/mL (HRF 25 and 50 µg/mL) in 3T3-L1 cells and delineate its possible mechanism of action. Materials and methods: Pre adipocyte 3T3-L1 cells were differentiated in the presence and absence of HRF 25 and 50 µg/mL, their lipid accumulation was measured qualitatively by Oil red O staining and quantitatively by triglyceride estimation. Effect on adipolysis was determined, adipogenic and its regulatory gene and protein expression were studied and effect of HRF 25 and 50 µg/mL on AMPK was confirmed in the presence of dorsomorphin. Results: Treatment with HRF 25 and 50 µg/mL activated AMP-activated protein kinase (AMPK) and was found to alleviate triglyceride accumulation significantly (p < 0.001) by 1.6 and 2.3 times respectively in pre adipocytes during differentiation. HRF 25 and 50 µg/mL also nonsignificantly reduced lipolysis which releases free fatty acids, a major contributing factor for insulin resistance. Activation of AMPK by phosphorylation has led to reduced gene and protein expression of adipogenic factors Peroxisome proliferator- activated receptor gamma (PPAR-γ), CCAT/enhancer binding protein alpha (C/EBPα), Sterol regulatory element- binding protein-1c (SREBP-1c) and their targets Fatty acid binding protein 4 (FABP4), Fatty acid synthase (FAS), Perilipin and enhanced Adiponectin expression. Treatment with HRF 25 and 50 µg/mL also resulted in inactivation of Acetyl-CoA carboxylase (ACC) by enhancing ACC phosphorylation, which reduced the levels of malonyl-CoA an allosteric inhibitor of carnitine palmitoyl transferase 1 (CPT1). Enhanced CPT1 levels causes induction of fatty acid β- oxidation. Effects of HRF were nullified in the presence of AMPK antagonist dorsomorphin. Conclusion: In summary, HRF treatments reduced adipogenesis, enhanced factors regulating fatty acid oxidation and this is mediated by AMPK activation. The results conclusively showed anti-obesity potential of HRF and it might be helpful in treatment of associated complications. Graphical abstract: fx1